2014
DOI: 10.1016/j.sbspro.2013.12.594
|View full text |Cite
|
Sign up to set email alerts
|

Panel Data Analysis of Foreign Direct Investment and Poverty from the Perspective of Developing Countries

Abstract: The purpose of this paper is to assess the relationship between foreign direct investment (FDI) and poverty at the macro-pathway in selected developing countries. The contribution to host countries from FDI can take several forms, such as the transfer of technology, human capital development, increased competition in domestic markets, and the generation of corporate tax revenues, among others. The paper develops a data set and an econometric model to analyse FDI flows and poverty relations at the macro level p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 1 publication
8
51
0
2
Order By: Relevance
“…According to prior literature, three findings from past studies can be obtained regarding the direct impact of FDI on poverty reduction, first portion of studies conclude that FDI has a positive impact on poverty reduction (e.g. Fowowe & Shuaibu, 2014;Gohou & Soumare, 2012;Israel, 2014;Shamim et al, 2014;Ucal, 2014;Soumare, 2015). Similarly, few studies conclude that there is a negative impact of FDI on poverty reduction (e.g.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…According to prior literature, three findings from past studies can be obtained regarding the direct impact of FDI on poverty reduction, first portion of studies conclude that FDI has a positive impact on poverty reduction (e.g. Fowowe & Shuaibu, 2014;Gohou & Soumare, 2012;Israel, 2014;Shamim et al, 2014;Ucal, 2014;Soumare, 2015). Similarly, few studies conclude that there is a negative impact of FDI on poverty reduction (e.g.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The study of Hunady and Orviska (2014) also presented evidence that supports the assumption that financial and economic crises will have a negative effect on FDI. In another study on developing countries, Ucal (2014) focused on the relationship between FDI and poverty. Their results showed that there is a statistically significant relationship between FDI and poverty, and it is obvious that FDI reduces poverty in selected developing countries.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Studies that have found a positive impact of FDI on poverty reduction include Hung (1999), Jalilian and Weiss (2002), Calvo and Hernandez (2006), Reiter and Steensma (2010), Gohou and Soumare (2012), Zaman et al (2012), Mahmood and Chaudhary (2012), Fowowe and Shuaibu (2014), Shamim et al (2014), Ucal (2014), Bharadwaj (2014), Israel (2014) Soumare (2015), and Uttama (2015). Hung (1999) analysed the relationship between FDI and poverty between 1992 and 2002 in a sample of 12 provinces and cities in Vietnam.…”
Section: A Review Of the Empirical Literature On The Impact Of Fdi Onmentioning
confidence: 99%
“…Using time series data, they found FDI to reduce poverty, just like Fowowe and Shuaibu (2014) and Jalilian and Weiss (2002). Ucal (2014) analysed the impact of FDI on poverty in a sample of 26 developing countries, using unbalanced panel analysis for the period between 1990 and 2009. He found a negative impact of FDI on poverty in selected countries, thus confirming that FDI plays a role in reducing poverty in these selected countries.…”
Section: A Review Of the Empirical Literature On The Impact Of Fdi Onmentioning
confidence: 99%